2006
DOI: 10.3998/ark.5550190.0007.f13
|View full text |Cite
|
Sign up to set email alerts
|

QSPR correlations of half-wave reduction potentials of cata-condensed benzenoid hydrocarbons

Abstract: Polarographic half-wave reduction potentials of 31 cata-condensed benzenoid hydrocarbons were estimated by using lowest unoccupied molecular orbital energies (E LUMO ), an indicator of the number of linearly-fused benzenoid rings (n), and distance-based topological indices. The first two parameters account for most of the variance. A parallelism between experimentally measured measured Diels-Alder reactivity and polarographic half-wave reduction potentials is illustrated by a correlation between these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In a recent paper, it was shown that the half-wave reduction potentials of catafusenes are correlated satisfactorily with n (one plus the number of adjacent zeros in the code) and the total number h of benzenoid rings . For naphthalene, we postulate that n = 0.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a recent paper, it was shown that the half-wave reduction potentials of catafusenes are correlated satisfactorily with n (one plus the number of adjacent zeros in the code) and the total number h of benzenoid rings . For naphthalene, we postulate that n = 0.…”
Section: Introductionmentioning
confidence: 82%
“…7 In a recent paper, it was shown that the half-wave reduction potentials of catafusenes are correlated satisfactorily with n (one plus the number of adjacent zeros in the code) and the total number h of benzenoid rings. 8 For naphthalene, we postulate that n ) 0. In the present paper, a quantitative structureproperty relationship (QSPR) study for other physical properties of catafusenes is presented.…”
Section: Introductionmentioning
confidence: 99%